Pengaruh Penggunaan Metode Cooperative Integrated Reading and Composition (CIRC) terhadap Keterampilan Literasi Informasi ditinjau dari Hasil Belajar Sejarah Siswa - Ila Samsiah; Yani Kusmarni (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2021)
This research was motivated by the low information literacy skills of students. This can be seen from the low skills of students in finding, processing, and presenting information. These skills can be seen through learning outcomes, because learning outcomes are a measure of the success of the learning process. Therefore, this study entitled